Combining the DNA methylation markers of circulating tumor cells with immune infiltrating cells to assess recurrence and prognosis and to suggest a therapeutic strategy in stage III-IV colorectal cancer - Zhou, Juan; Ye, Danli; Li, Yuansen; Lai, Xuwen; Cui, Wenzhi; He, Wenyuan; Yu, Ling; Wu, Jingyi; Yan, Guangning; Lei, Chengyong; Wang, Wei (Frontiers in Immunology, 2025)
IntroductionCirculating tumor DNA (ctDNA) methylation markers show potential for early detection of cancer metastasis. This study aimed to identify ctDNA methylation markers predictive of recurrence and prognosis in colorectal cancer (CRC) patients, and to explore the influence of the tumor immune microenvironment on outcomes.MethodsWe analyzed 603 overlapping methylation markers from both plasma and tissue samples and developed a risk model to predict CRC recurrence and prognosis.ResultsZNF671 and ZNF132 were identified as key methylation markers. The model predicted relapse risk in stage III CRC patients with an AUC of 0.90 and prognosis in stage IV patients. High-risk patients exhibited a significantly higher early relapse rate (75.4% vs. 20%) and were more likely to have a low Immunoscore (IS), which correlates with poorer prognosis.DiscussionZNF671 and ZNF132 methylation levels inversely correlate with Immunoscore and may serve as valuable biomarkers for CRC immunotherapy. These findings provide insights for improved prognostic evaluation and personalized treatment strategies.